2007
DOI: 10.1037/h0100381
|View full text |Cite
|
Sign up to set email alerts
|

The effects of daily intensive tact instruction on the emission of pure mands and tacts in non-instructional settings by three preschool children with developmental delays.

Abstract: We tested the effects of an intensive tact instruction procedure on the emission of verbal operants in non-instructional settings by three preschool students with developmental delays. The participants were selected because they emitted low numbers pure verbal operants in non-instructional settings throughout the school day. Specifically, we measured the number of pure mands and tacts emitted during probes in the non-instructional settings. During the intensive tact procedure, the participants received an addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
2
15
0
1
Order By: Relevance
“…Greer et al (cf. Greer et al, 2017) have identified at least three types of procedures that have been demonstrated to establish BiN in children who have not shown such skills prior to the intervention: (a) multiple-exemplar instruction (MEI; Fiorile & Greer, 2007), (b) the intensive tact protocol (ITP; Greer & Du, 2010;Pereira-Delgado & Oblak, 2007;Pistoljevic & Greer, 2006;Schauffler & Greer, 2006;Schmelzkopf, Singer-Dudek, & Du, 2017), and (c) conditioning stimuli as reinforcers for observing responses (Longano & Greer, 2015).…”
mentioning
confidence: 99%
“…Greer et al (cf. Greer et al, 2017) have identified at least three types of procedures that have been demonstrated to establish BiN in children who have not shown such skills prior to the intervention: (a) multiple-exemplar instruction (MEI; Fiorile & Greer, 2007), (b) the intensive tact protocol (ITP; Greer & Du, 2010;Pereira-Delgado & Oblak, 2007;Pistoljevic & Greer, 2006;Schauffler & Greer, 2006;Schmelzkopf, Singer-Dudek, & Du, 2017), and (c) conditioning stimuli as reinforcers for observing responses (Longano & Greer, 2015).…”
mentioning
confidence: 99%
“…Com a busca nas bases de dados, não foram encontrados estudos que utilizassem esse procedimento. Adicionalmente, os artigos citados como exemplos da efetividade do referido protocolo não avaliam diretamente a indução de BiN, mas sim, de forma geral, a emissão de operantes verbais, como tatos e mandos, de forma espontânea em contextos não instrucionais (Delgado & Oblak, 2007;Greer & Du, 2010;Pistoljevic & Greer, 2006;Schauffler & Greer, 2006;Schmelzkopf et al, 2017). Embora o ensino de tato tenha eficácia comprovada para a indução de Nomeação unidirecional de ouvinte, mais estudos são necessários para ampliar o conhecimento sobre as variáveis presentes no protocolo de tato intensivo e sua possível relação com a indução dos diferentes subtipos de BiN.…”
Section: Discussionunclassified
“…Discrete trial training (DTT) is a behavior analytic instructional procedure that has been shown to foster acquisition of tacts by children with an ASD and other developmental delays (e.g., Delgado & Oblak, 2007; LaLonde, 2020; Partington et al., 1994). However, most previous studies evaluating acquisition of tacts have focused on tacts of static stimuli (e.g., nouns) and few studies assessed acquisition of tacts of dynamic stimuli (e.g., actions) (Schebell et al., 2017).…”
mentioning
confidence: 99%